Factors Associated With The Incidence Of Hypertension In Young Adults At Pasar Ikan Community Health Centre, Bengkulu City, 2024 - Ahmad Zubiyo; Tuti Rohani; Handi Rustandi (Multidisciplinary Journals, 2025)
Hypertension is a condition where systolic blood pressure ≥ 140 mmHg and diastolic pressure ≥ 90 mmHg. In general, hypertension does not provide typical complaints and symptoms so that many sufferers are not aware of it. Therefore, hypertension is said to be the silent killer. This study aims to determine the factors related to the incidence of hypertension in young adults. The method used was descriptive quantitative with a cross sectional design, data were collected by distributing questionnaires to 66 respondents who visited the general clinic of Pasar Ikan Health Center in Bengkulu City, the sampling technique used purposive sampling. The results of the univariate test analysis that most of the respondents (56.1%) were aged 18-40 years, most of the respondents (66.7%) had a family history, most of the respondents (57.6%) did not smoke and most of the respondents (56.1%) were hypertensive. Bivariate analysis results Age gets a p value (0.620) which shows no correlation, family history gets a p value (0.035) which shows there is a correlation, smoking habits get a p value (0.804) which shows no correlation. Researchers suggest that the Pasar Ikan Health Center be able to provide services and provide counseling on factors related to the incidence of hypertension.